2021
DOI: 10.1007/s40264-021-01107-6
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Trial and Postmarketing Safety of Onasemnogene Abeparvovec Therapy

Abstract: Introduction This is the first description of safety data for intravenous onasemnogene abeparvovec, the only approved systemically administered gene-replacement therapy for spinal muscular atrophy. Objective We comprehensively assessed the safety of intravenous onasemnogene abeparvovec from preclinical studies, clinical studies, and postmarketing data. Methods Single-dose toxicity studies were performed in neonatal mice and juvenile or neonatal cynomolgus nonhuman primates (NHPs). Data presented are from a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 32 publications
4
86
0
6
Order By: Relevance
“…The longer-term effects of combined therapy however require evaluation. 20 Whilst transaminitis and thrombocytopaenia were observed across our cohort as seen in prior studies, 6,21 we observed a greater extent of liver and platelet dysfunction in children weighing ≥8 kg. We also observed a bimodal rise in liver enzymes with one peak occurring relatively acutely following therapy.…”
Section: Discussionsupporting
confidence: 70%
“…The longer-term effects of combined therapy however require evaluation. 20 Whilst transaminitis and thrombocytopaenia were observed across our cohort as seen in prior studies, 6,21 we observed a greater extent of liver and platelet dysfunction in children weighing ≥8 kg. We also observed a bimodal rise in liver enzymes with one peak occurring relatively acutely following therapy.…”
Section: Discussionsupporting
confidence: 70%
“…Hepatotoxicity events resolved over time with prednisolone treatment. Transient decreases in platelets (<75,000 cells/µL) were also observed after vector administration 16 . In the post-marketing setting, transient hepatotoxicity, including four cases of acute liver failure, was the most common adverse event (AE).…”
Section: Mainmentioning
confidence: 89%
“…A recent analysis summarized onasemnogene abeparvovec safety data from seven clinical trials ( n = 102) as well as post-marketing reports ( n = 665) through 12 November 2020 16 . In clinical trials, liver transaminases increased transiently in 90 of 102 (90%) patients and, in some cases, exceeded three times the upper limit of normal (ULN) (9% mild ≥3× ULN to <5× ULN; 6% ≥5× to <20× ULN; and 5% ≥20× ULN) 17 .…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased SMN protein expression following the treatment has successfully prevented the death of motor neurons with the improvement of neuromuscular functions in the affected children. The phase 3 trial provides promising outcomes and Onasemnogene abeparvovec (Zolgensma ® ) was approved by the FDA in 2019 [ 146 , 147 ]. Recently, a matching-adjusted indirect comparison study between Onasemnogene abeparvovec and Nusinersen found that, in terms of event-free survival, overall survival, and motor milestone achievement, Onasemnogene abeparvovec provides a continuous benefit compared to Nusinersen in 24 months follow-up [ 148 ].…”
Section: Rna Therapies To Treat Single-gene Neurological Disordersmentioning
confidence: 99%